2021
DOI: 10.1177/10778012211051399
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Determinants of Gambling-Related Intimate Partner Violence: Perspectives From Women Who Gamble

Abstract: Rates of intimate partner violence (IPV) victimization are higher among women with a gambling problem. However, women's experiences of this violence, from a gendered perspective, have not been examined. Based on interviews with 24 women, this study explored how problem gambling contributes to IPV against women across three levels of influence. Findings reveal that problem gambling did not directly cause IPV, but interacts where gendered drivers and reinforcers are present to exacerbate this violence. Reducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 50 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…A gender-based perspective may help to shift gambling research beyond its predominantly situational violence perspective that assumes that all DFV/IPV arises from escalating conflicts in relationships, to also recognize the use of power and control in violent relationships ( Bender, 2017 ). This shift is evident in some qualitative gambling research ( Hing et al, 2021 , 2022a , 2022b , 2022d , 2022c ; Banks and Waters, 2022 ; O’Mullan et al, 2022a ), but not in the quantitative measures used. Gambling research should examine IPV perpetrated by men against women, by women against men, and in same-sex relationships, using approaches and instruments that are sensitive to different conceptualizations, experiences, and reporting of violence in these contexts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A gender-based perspective may help to shift gambling research beyond its predominantly situational violence perspective that assumes that all DFV/IPV arises from escalating conflicts in relationships, to also recognize the use of power and control in violent relationships ( Bender, 2017 ). This shift is evident in some qualitative gambling research ( Hing et al, 2021 , 2022a , 2022b , 2022d , 2022c ; Banks and Waters, 2022 ; O’Mullan et al, 2022a ), but not in the quantitative measures used. Gambling research should examine IPV perpetrated by men against women, by women against men, and in same-sex relationships, using approaches and instruments that are sensitive to different conceptualizations, experiences, and reporting of violence in these contexts.…”
Section: Discussionmentioning
confidence: 99%
“…In Suomi et al’s (2013) study, the 11 interviewees who had perpetrated violence against a family member reported that their violence was fueled by their accumulated anger and mistrust arising from the victim’s gambling. However, perpetrators’ explanations for their violence are unreliable, since they frequently use victim-blaming and external “causes” to justify their violence ( Henning and Holdford, 2006 ), including blaming the victim’s gambling ( Browne et al, 2016 ; Hing et al, 2020 ; O’Mullan et al, 2022a ). Nevertheless, problem gambling undoubtedly has deleterious effects on families.…”
Section: Dfv/ipv Linked To a Victim’s Gamblingmentioning
confidence: 99%
See 3 more Smart Citations